2017
DOI: 10.1192/bjp.bp.116.187179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antenatal and postnatal anxiety: Systematic review and meta-analysis

Abstract: Maternal anxiety negatively influences child outcomes. Reliable estimates have not been established because of varying published prevalence rates.To establish summary estimates for the prevalence of maternal anxiety in the antenatal and postnatal periods.We searched multiple databases including MEDLINE, Embase, and PsycINFO to identify studies published up to January 2016 with data on the prevalence of antenatal or postnatal anxiety. Data were extracted from published reports and any missing information was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
679
24
30

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 981 publications
(829 citation statements)
references
References 86 publications
37
679
24
30
Order By: Relevance
“…In their systematic review, Sawyer et al [43] reported a 14.8% prevalence of anxiety in infertile women [95% CI: 12.3, 17.4%] and a 14% prevalence among women in pre-and post-natal periods [95% CI: 12.9, 15.2%]. In a meta-analysis conducted by Dennis et al [44], the prevalence of selfreported anxiety symptoms was 18.2% (95% CI: 13.6-22.8) in the first trimester of pregnancy, 19.1% (95% CI: 15.9-22.4) in the second trimester of pregnancy, 24.6% (95% CI: 21.2-28.0) in the third trimester of pregnancy, and 15.0% (95% CI: 13.7-16.4) in the first to 14th weeks of the post-natal period.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Sawyer et al [43] reported a 14.8% prevalence of anxiety in infertile women [95% CI: 12.3, 17.4%] and a 14% prevalence among women in pre-and post-natal periods [95% CI: 12.9, 15.2%]. In a meta-analysis conducted by Dennis et al [44], the prevalence of selfreported anxiety symptoms was 18.2% (95% CI: 13.6-22.8) in the first trimester of pregnancy, 19.1% (95% CI: 15.9-22.4) in the second trimester of pregnancy, 24.6% (95% CI: 21.2-28.0) in the third trimester of pregnancy, and 15.0% (95% CI: 13.7-16.4) in the first to 14th weeks of the post-natal period.…”
Section: Discussionmentioning
confidence: 99%
“…Women continue to give birth which is usually a time of joy but can also be associated with increased anxiety as well as increased risk of wellbeing disturbances, both during pregnancy and after birth [6]. Maternity service providers (including doctors, midwives, nurses and allied health staff) must continue their core business in caring and supporting women, newborns and their families, whilst also adapting to a rapidly changing health system environment due to COVID-19.…”
Section: Issues For Maternity Care Providersmentioning
confidence: 99%
“…Indeed, some recent evidence suggests that anxiety disorders are more prevalent than depression in the post-partum period [6]. Reports of the prevalence of postnatal anxiety [7] have prompted calls for “a broader definition of post-partum distress” [4, p. 329] that includes anxiety as well as depression. The significant comorbidity of depression and anxiety is well established, adding further weight to the argument for focusing on a range of psychological conditions in new mothers.…”
Section: Introductionmentioning
confidence: 99%